2016
DOI: 10.4143/crt.2015.463
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Risk Factors for Transient and Persistent Lymphedema after Multimodal Treatment for Breast Cancer

Abstract: PurposeThe purpose of this study is to identify risk factors for transient lymphedema (TLE) and persistent lymphedema (PLE) following treatment for breast cancer.Materials and MethodsA total of 1,073 patients who underwent curative breast surgery were analyzed. TLE was defined as one episode of arm swelling that had resolved spontaneously by the next follow-up; arm swelling that persisted over two consecutive examinations was considered PLE.ResultsAt a median follow-up period of 5.1 years, 370 cases of lymphed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 19 publications
(37 reference statements)
3
59
3
4
Order By: Relevance
“…Furthermore, the limited length of follow-up and the lack of interim measurements prevented differentiation between persistent and transient swelling, although the probability of transient swelling increases by only 2% after 1 year. 32 We would, however, expect additional cases of persistent lymphedema because the lymphedema incidence has been found to be 15% from 6 to 12 months after surgery and 19% from 12 to 24 months after surgery. 3 Lastly, the level of physical activity among the women who participated in this study was high, and this may limit the generalizability of the results to physically inactive women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the limited length of follow-up and the lack of interim measurements prevented differentiation between persistent and transient swelling, although the probability of transient swelling increases by only 2% after 1 year. 32 We would, however, expect additional cases of persistent lymphedema because the lymphedema incidence has been found to be 15% from 6 to 12 months after surgery and 19% from 12 to 24 months after surgery. 3 Lastly, the level of physical activity among the women who participated in this study was high, and this may limit the generalizability of the results to physically inactive women.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment measurement would be preferable, but because the ALND procedure was not always known preoperatively, we did not consider this an option. Furthermore, the limited length of follow‐up and the lack of interim measurements prevented differentiation between persistent and transient swelling, although the probability of transient swelling increases by only 2% after 1 year . We would, however, expect additional cases of persistent lymphedema because the lymphedema incidence has been found to be 15% from 6 to 12 months after surgery and 19% from 12 to 24 months after surgery .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify whether the swelling is transient or persistent. In one study, it was reported that one-third of initial swelling attacks were transient (10). Since effective treatment of LE can be established in early stages, accurate and timely diagnosis is crucial (11).…”
Section: Diagnosismentioning
confidence: 99%
“…Although there is no unique sign or criteria for defining LE, the diagnosis is usually made clinically by thorough evaluation and physical examination (2,3,10). Family history is important in the diagnosis of primary LE.…”
Section: Diagnosismentioning
confidence: 99%
“…The incidence rate of postoperative complications such as pain, lymphedema, numbness or motility disorders differs between sentinel node biopsy and axillary lymph node dissection (16,17). It has been reported that chemotherapy with taxanes and radiation covering the breast and supraclavicular region were independent risk factors for lymphedema (18,19). Generally, MBC is potentially resistant to chemotherapy or radiotherapy (1,2,4).…”
Section: Mbc No (%) -----------------------------------------------mentioning
confidence: 99%